Prevalence of long QTc interval in methadone maintenance patients - Fonseca, Francina; Marti-Almor, Julio; Pastor, Antoni; Cladellas, Mercè; Farré, Magí; de la Torre, Rafael; Torrens, Marta (Drug and alcohol dependence, 2009)
There is a concern about cardiac rhythm disorders related to QTc interval prolongation induced by methadone. A cross-sectional study was designed to evaluate the prevalence of long QTc (LQTc) interval in patients in methadone maintenance treatment (MMT) and risk factors for LQTc. The study population included 109 subjects (74 males, median age 43 years). Socio-demographic and toxicological variables were recorded, as well as concomitant use of drugs related with QT prolongation, history of heart diseases, and corrected QT interval by heart rate (QTc) in the ECG. Plasma concentrations of (R)-methadone and (S)-methadone enantiomers were determined in 69 subjects. Ten patients (9.2%) presented a QTc above 440ms but a QTc above 500ms was observed in only 2 (1.8%). Patients with QTc above 440ms compared with the remaining subjects were older (median [25th–75th percentile range]: 49 [39–56] years vs. 37 [33–43]; Wilcoxon's W=217.5, p=0.002) and took a higher daily dose of methadone (median [25th–75th percentile range]: 120 [66–228]mg/day vs. 60 [40–110]mg/day; W=298.5, p=0.037). Methadone dose correlated with QTc interval (Pearson's r2=0.291, p=0.002). Patients with and without long QTc showed no differences in plasma concentrations of (R)-methadone and (S)-methadone enantiomers. The prevalence of LQTc was 9.2%. An association between LQTc and methadone doses was observed but the relationship with plasma concentrations of methadone enantiomers is unclear.